المضامين العقدية للامثال الشعبية في منطقة وادي سوف -دراسة تحليلية - اليمان, جهاد; عليلي, حفصة (University Of Eloud جامعة الوادي, 2019)
"إن دراستنا الموسومة ""بالمضامين العقدية للأمثال الشعبية بمنطقة وادي سوف دراسة تحليلة"" هي دراسة للأمثال الشعبية في ضوء العقيدة الإسلامية للإجابة على إشكالية الموافقة والمخالفة لها، حيث تضمنت الدراسة –بعد الاستقراء الواسع والتصنيف والاختيار- خمسة وثلاثون مثلاً، تمّ ذكرها وحصرها مما يتداول بالمنطقة، تمحورت بعد تصنيفها على أساسٍ موضوعي حول أركان ثلاثة من أركان الإيمان الستة: الإيمان بالله، اليوم الآخر، والقضاء والقدر. وبعد الوقوف على المعنى اللغوي، ثم تحديد مراد ومضرب كل المثل بالاستعانة بالخبراء الذين أجريت معهم المقابلات العلمية، وببعض المصادر العلمية في الموضوع ومعاجم اللغة العربية؛ خلصنا إلى الحكم الدقيق على المثل المضروب في لفظه ومعناه، في ميزان الموافقة أو المخالفة للعقيدة الإسلامية. وكانت النتيجة هي الوقوف على جملة من الموافقات والمخالفات للعقيدة الإسلامية لتلك الأمثال المحددة للدراسة، والخلوص إلى أهمية الأمثال كقالب لغوي يحمل مضامين التواصل بين الناس، وضرورة العناية بها استثمارا في تبليغ كثير من الأسس العقائدية من جهة، وتصحيح ما قد يشوبها في بمختلف وجوه مضامينها. ومن جهة أخرى تكون هذه الدراسة دعوة إلى التدقيق والتمحيص المفضي إلى إمكانية الاستشهاد بالأمثال ذات المضمون الموافق للعقيدة فيما فيه حاجة وفائدة لاستعماله، وكذا إيضاح التدقيق والحذر والنهي الواجب من استعمال الأمثال المخالفة للعقيدة الإسلامية. " "Our study known by ""the religions meanings of popular proverbs in Ouad-Souf analytic study"". It is the study of the popular) clematic( proverbs on the basis of Islamic religion )faith(. It aims at answering the question of the bact that whether these proverbs agree or disagree with the religion after a broad induction, classification and selection, this study has consisted of thirty five )35( mentioned and limited proverbs used in Ouad-Souf. After classifying them on the basis of theme, focus on three among six pillars of Islamic belief )faith(. These pillars are the belief in Allah, belief in the judgment day )eternal lif( and destiny. After focusing on the linguistic meaning, we decided the meaning and the place of each proverb. This decision was with the help of expert in scientific meeting, scientific references. We came to the precise judgement on the parol and the meaning of the given proverbs in terms of agreement and disagreement with Islamic belief )faith(.We also came to the conclusion that proverbs are an important linguistic form including communicative meanings among people. It’s them, invest them in communicating many religions principles and correct what may worsen their different meanings on one hand. On the other hand, this study is an invitation to precision and check which lead to the possibility of justifying with proverbs which meaning fully agree with the Islamic religion )faith( and meet the need of people. It is also an invitation to classifying precision, being prudent and prohibiting people from the use of proverbs which meaning fully disagree with the Islamic religion )faith(. "
مذكرة ماستر تخصص عقيدة إسلامية
Keywords: المضامين العقدية-الأمثال الشعبية-الإيمان بالله-; Nodal implications - popular proverbs - belief in God -